Cases and materials in revenue law - Easson, A. J. (London : Sweet and Maxwell, 1973)
This book examines the concept of revenue law. It is grouped into four areas: principles of revenue law; taxes on income and gains; taxable persons and estate duty.
Includes index.
lje 25/01/2019
Loans
Keywords: Taxation; Revenue law; Tax law